NATIONAL POLICY OF EDUCATION 2020 AND ITS IMPACT ON HIGHER EDUCATION (International Journal of Food and Nutritional Sciences, 2023)
Education plays an important role for all round development of an individual. It helps in the socialization of people in the society. The National Policy of Education 2020 came after 34 years and is all set to change the existing academic system of india. The purpose is to make the international standard of academic in the entire India. Its biggest impact would be the change in the learning environment as well as learning process of the students which will open up new learning opportunities. The policy is a comprehensive framework from primary to higher education. It has framework for vocational training as well. The New Education Policy will increase the focus on the skill development and competency of the students. It focuses on making learning more inclusive, flexible, focused on 21st century skills which will be enjoyable for all students in any age group. The policy aims to transform teaching methodologies, school curriculum and student assessments. However, the education policy has impacted school and school education, similarly, this paper mostly centers around NEP2020 and its impact on higher education. So, this paper traces the conspicuous elements of NEP and investigations they mean for the current education system.